Bilder fur den Pharao : Untersuchungen zu den bildlichen Ausdrucken des Agyptischen in den Konigsinschriften und anderen Textgattungen - Hsu, Shih-Wei. (Probleme der Ägyptologie, 2017)
In Bilder für den Pharao Shih-Wei HSU offers a thorough study of figurative expressions in ancient Egyptian texts, placing particular emphasis on royal inscriptions. This book is divided into three chapters. Chapter one consists of an introduction to the study of figurative language, examining the definition of this construct and discussing the differences between similes and metaphors in ancient Egyptian. Chapter two provides an overview of usage, function and purpose of figurative language in the different text genres. Chapter three contains the research and analysis of the figurative language found in the royal inscriptions. It acts as linguistic "decoration" for the king's attributes and actions, reinforcing and sustaining the notion of kingship in Egypt.